Literatur Review : Penerapan Sistem Informasi Penggajian Karyawan Berbasis Web: Studi Literatur Dari Sebuah Perusahaan - Fawwazi Arsyad, Naufal; Arif , Muhammad; Prastya, Indra; Ramadhani Airmas Sahid, Rubby; Heidiani Ikasari, Ines (CV. Shofanah Media Berkah, 2024)
In this study, we will look at five journals that deal with the development of web-based information systems. We focus on new trends, technology, and how this affects human capital. Web-based information retrieval systems have become an increasingly important solution for improving the efficiency and accuracy of retrieval in many businesses. According to research, many techniques, including as prototyping and extreme programming, as well as the use of PHP and MySQL databases, may be used to create systems that meet the needs of a business. This study found that using a web-based information management system not only improves accuracy and efficiency, but also makes data management easier. As a result, organizations may focus more on achieving better results and growing human capital. As a result, this training provides valuable knowledge for researchers and practitioners who want to implement a more effective and efficient system of measurement.